INVESTASI SUKUK: PERSPEKTIF EKONOMI SYARI’AH - HULWATI HULWATI (JEBI (Jurnal Ekonomi dan Bisnis Islam), 2017)
The theme of the article is "economy based on the principles of Islam". Investment of sukuk was a solution of investment of conventional bonds. It is not allowed in shari’a, because of riba. Sukuk will be able to offer the innovative financial solution, this is product not only give a good contribution to the investment but also sukuk was be capable to compete with anothers investment in capital market. Moreover this investment is considered by company as alternative to get fund. Based on the explanation above, how investment of sukuk, wether sukuk is allowed by Islamic economic pespective or not? In this paper, I elaborate how the legal concept of invesment in Islamic economic perspective. Then I concentrate to describe about the concept of sukuk, also explain on mecanism of transaction of sukuk. Last, I attempt to analyze how the investment of sukuk in Islamic economic perspective.